(untitled) (Global Journal of Science Frontier Research, 2021)
In this paper we introduced the definition of perfect folding of graphs and we proved that cycle graphs of even number of edges can be perfectly folded while that of odd number of edges can be perfectly folded to C3. Also we proved that wheel graphs of odd number of vertices can be perfectly folded to C3. Finally we proved that if G is a graph of n vertices such that 2 > clique number = chromatic number = k > n, then the graph can be perfectly folded to a clique of order k.